In-silico screening of potential targets from wound healing pathways against Hordenine and selected Bioisostere - S.Amsaveni, S.Radha Mahendran, G.Surya, Umashankar Vetrivel, Luke Elizabeth Hanna (South Eastern European Journal of Public Health, 2025)
Hordenine (4-[2-(Dimethylamino) ethyl] phenol) a plant-based phenethylamine alkaloid and its shortlisted bioisostere 1-(5-amino-1H-1,2,4-triazol-3-yl)-N-[2-(4-chlorophenyl) ethyl]-N-methylpiperidin-4-amine, which showed nil-lead likeliness violation during ADMET screening were docked with eight potential drug targets from selected wound healing pathways. The results showed that Metalloproteinase-9 and Proliferating cell antigen had the lowest binding energy of -6.23 and -6.58 kcal/mol, respectively. However, when considering the molecular interactions were considered, Tyrosine related protein 1 had the maximum number of interactions with binding energy of -5.83 kcal/mol and the highest number of hydrogen bonds. The molecule 1-(5-amino-1H-1,2,4-triazol-3-yl)-N-[2-(4-chlorophenyl)ethyl]-N-methylpiperidin-4-amine docked well with all the targets and had appreciably lower binding energies for all the wound healing targets: Casein kinase 1 -14.41Kcal/mol, Metalloproteinase-9 -11.7241Kcal/mol, Proliferating cell antigen -9.8941Kcal/mol, Tyrosine related protein 1 -9.4441Kcal/mol, ß2 adrenergic receptors -8.1941Kcal/mol, Notch1 I D receptor -7.4441Kcal/mol, Dopachrome tautomerase -6.4 41Kcal/mol and Glycogen synthase kinase 3 beta -5.741Kcal/mol. The Molecular dynamic simulations of Casein kinase 1 with 1-(5-amino-1H-1,2,4-triazol-3-yl)-N-[2-(4-chlorophenyl) ethyl]-N-methylpiperidin-4-amine showed that the Cα Root mean square deviation values were within 1.6 Å throughout the simulation for the system and the root mean square fluctuations showed that loop residues (Residues 49 to 57) involved in ligand binding had minimal fluctuations as compared to the other loop residues. A free binding energy of -10.44 Kcal /mol was derived from MMPBSA calculations and this corroborated well with the good binding score obtained by docking. This shows that the protein-ligand complex did not undergo any major conformational change and was stable throughout the simulation giving supportive evidence that this molecule could be a promising candidate for acute and chronic wound healing including diabetic foot ulcers, along with Hordenine which is an effective inhibitor of hyperpigmentation.